Percepção e experiência de um viajante: relatos do programa ciência sem fronteiras na perspectiva do ensino de engenharia - Leal, Públio Quirino (Universidade Federal Rural do Semi-Árido, 2017)
The Science Without Borders program was born to enable the internationalization of Brazilian’s science and technology possible, making our universities more and more competitive, however, after the return of several groups of Brazilian students from the exchanging program arises a serious problem that is the very limited use of the empirical knowledge and experiences owned by these students diffused in the academic universe of our country. This work aims to make a technical and theoretical study about the perception and experience of a scholarship holder of the Sciences without Borders program from the perspective of engineering educational system in the USA/Brazil. The methodology was based on the literature review and data collection in primary and secondary sources related to the research’s main questions, field research consisting of collecting data from former scholarship holders highlighting their respective contributions after the end of the program, tabulation of data obtained, that subsidized the considerations and conclusive arguments of the work, in the light of the bibliographical reference. The results showed the advantages and disadvantages of participating in the program, as well as providing a socioeconomic profile of the former scholarship holders, besides indicating the lack of preparation of the Brazilian educational system for the use of the knowledge acquired abroad. In the research there are also complicating elements for the graduating students, as the difficulty in the use of disciplines back in Brazil. As a conclusion, a series of short- and long-term actions were set out that could make SwB more viable, both from a personal and academic point of view.
Keywords: Relato; percepção; ciência sem fronteiras; engenharia; estados unidos; report; perception; science without borders; engineering; united states of america; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA